THE REALIZATION OF STUDENTS’ POLITE REJECTION SPEECHES - Fatmawati; Endry Boeriswati; Zuriyati (Getsempena English Education Journal, 2020)
This research aims to obtain a deep understanding of the realization of polite rejection speech of the Literature Education students at the FKIP UIR. The data sources in this research were all polite rejection speeches expressed by the students. This research used the descriptive qualitative method with a phenomenology approach. The results show that polite rejections are more dominant used with reasons. It shows that giving a reason when rejecting an offer, invitation, command, and appeal would be considered more appropriate and does not hurt the interlocutors. It also shows a scale of unreadiness. Further, the scale of unreadiness may be an alternative that can be applied when performing rejection speeches. This indicates that the rejection speeches expressed by the students are classified as polite.